KOMPETENSI KEPRIBADIAN GURU PAI DALAM MENGEMBANGKAN RANAH AFEKTIF SISWA DI MAN 2 MODEL MEDAN - Dedi Syahputra Napitupulu (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Competence is a mastery of a task, skill, attitude and appreciation necessary to support the quality of the profession. The ideal teacher should have four competencies, namely pedagogical, personality, social and professionalism. Personal competence with regard to personal behavior of teachers themselves who have noble values are reflected in everyday behavior. This is necessary for the purpose of education can be achieved as expected, mainly on changes in affective student. Because education is not just a transfer of knowledge and skills, but also how education is able to change the attitude and character of students. The purpose of this study was to look at the competence of the teacher's personality and the work done in developing the affective students as well as supporting factors and obstacles in developing affective students in MAN 2 Model Medan.Keywords: Competence, personality, teacher religion islam, affective